International Financial Statistics, December 2017. (International Financial Statistics; International Financial Statistics ;, 2017)
This paper describes the country, euro area, and world tables that provide measures of effective exchange rates, compiled by the IMF's Research Department, Statistics Department, and area departments. A nominal effective exchange rate index represents the ratio of an index of a currency's period-average exchange rate to a weighted geometric average of exchange rates for the currencies of selected countries and the euro area. A real effective exchange rate index represents a nominal effective exchange rate index adjusted for relative movements in national price or cost indicators of the home country, selected countries, and the euro area. For ease of comparison between the nominal effective exchange rate index and the real effective exchange rate index, the average exchange rate expressed in terms of US dollars per unit of each of the national currencies is also given in the index form, base 2010 equal to 100.